Al Ilmu Article Writing Guidelines: Journal Islamic Education Literature Review on Digital-Based Islamic Education Learning Planning through the TPACK Framework: Implications for Information Technology Literacy and Learning - Hasyim, Ade Hastuty; Hasmuddin, Hasmuddin; Dalle, Ambo; Jaswan, Jaswan; Halik, Abd (PT. Anagata Sembagi Education, 2025)
The integration of information and communication technology (ICT) in Islamic Religious Education (PAI) necessitates a systematic approach to lesson planning. This article reviews literature on digital-based PAI lesson planning through the Technological Pedagogical Content Knowledge (TPACK) framework, emphasizing the synergy of technological, pedagogical, and Islamic content knowledge. Analyzing 25 academic sources from 2005 to 2025, the study explores how TPACK supports curriculum design, teaching strategies, and evaluation in PAI. A case study on developing a Semester Lesson Plan (RPS) for the 2-credit course Information Technology Literacy and Learning in the PAI undergraduate program illustrates TPACK’s application. Findings indicate that TPACK enables educators to design effective, Islam-aligned learning, despite challenges like the digital divide and educators’ technological literacy. Research gaps exist regarding advanced technologies like artificial intelligence (AI) and virtual reality (VR) in PAI. Recommendations include curriculum development and teacher training to enhance information technology literacy in PAI.